Initial experience of dual maintenance immunosuppression with steroid withdrawal in vascular composite tissue allotransplantation - Diaz‐Siso, J. Rodrigo; Fischer, Sebastian (American journal of transplantation, 2015)
Current immunosuppression in VCA is largely based on the experience in solid organ transplantation. It remains unclear if steroids can be reduced safely in VCA recipients. We report on five VCA recipients who were weaned off maintenance steroids after a median of 2 months (mean: 4.8 months, range 2-12 months). Patients were kept subsequently on a low dose, dual maintenance consisting of tacrolimus and mycophenolate mofetil/mycophenloic acid with a mean follow-up of 43.6 months (median = 40 months, range 34-64 months). Early and late acute rejections responded well to temporarily augmented maintenance, topical immunosuppression, and/or steroid bolus treatment. One late steroid-resistant acute rejection required treatment with thymoglobulin. All patients have been gradually weaned off steroids subsequent to the treatment of acute rejections. Low levels of tacrolimus (<5 ng/mL) appeared as a risk for acute rejections. Although further experience and a cautious approach are warranted, dual-steroid free maintenance immunosuppression appears feasible in a series of five VCA recipients.